Adolescent Pregnancy among Ethnic Variants at Lumbini Medical College - Shrestha, Subha; Shrestha, Buddhi Kumar (Journal of Lumbini Medical College, 2016)
Introduction: Adolescent pregnancy is a common social phenomenon that results to both maternal and fetal related health consequences globally. Important factors affecting this high risk group of pregnancies are social, cultural, ethnic and racial disparities which may limit the care during pregnancy thereby affecting the perinatal outcome. The main objective of this study was to estimate the maternal and fetal outcome of adolescent pregnancies visiting Lumbini Medical college among ethnic variants of mid-western region. Methods: A retrospective observational study was conducted in Lumbini Medical College and Teaching Hospital for one year duration. Data was retrieved from the medical records of the admitted adolescent pregnant mothers with hospital delivery after 20 weeks’ gestation. Variables of interest were the selective demographic characteristics like place of residence and ethnicity of women, parity, and obstetrical &fetal outcomes. Results: The total numbers of admission for deliveries during the study period were 1905, out of which 462 (24.3%) were adolescent pregnancy. A total of 184 (39%) adolescent mothers were at the age of 19 and 334 (72.2%) of them were from Palpa district. The highest number of teenagers were from Janajati group i.e. 240 (52%). Among all, 38 (10%) had preterm delivery and 7 (1.5%) had intrauterine fetal death. While 407 (88.3%) adolescent pregnancies had vaginal deliveries, 54 (11.7%)of them had lower segment cesarean section (LSCS). Fifty-one (11.4%) neonates had low birth weight (below 2500 gm)and 11 (2.4%) had stillbirths. Among the low birth weight, 32 (51%) newborns were admitted to neonatal intensive care unit (NICU). Conclusions: Adolescent pregnancy is higher common in Palpa district of Nepal. Janajati adolescent girls are becoming pregnant early after marriage. Higher numbers of teenagers are 19 years of age and are primigravida. On reaching the tertiary center, obstetrical outcome is better with less maternal morbidity and no mortality and better neonatal survival. DOI: https://doi.org/10.22502/jlmc.v3i1.59